Faktor Determinan Stunting pada Balita : Tinjauan Literatur - Gusriani Gusriani; Nur Indah Noviyanti; Wahida Wahida; Ruqaiyah Ruqaiyah; Mega Octamelia (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2023)
Stunting is a condition of inhibited or stunted body growth caused by chronic malnutrition that is not addressed properly and promptly. Stunting is one of the nutritional problems that occur worldwide, including in Indonesia. There are many factors that can cause stunting. The purpose of this study is to review the factors that can lead to stunting in toddlers.The study was conducted by conducting a literature review through searching relevant articles from various electronic databases (Google Scholar, DOAJ, Pubmed, portal garuda) using keywords such as